Underlying factors contributing to child sexual abuse: a case study in Taman Seri Puteri Cheras, Kajang / Iffah Nabilah Ismail Mubarak - Ismail Mubarak, Iffah Nabilah (2019)
Sexual child abuse's trend has been on the rise in Malaysia. This social issue happens all over the world. From the statistic, the case of sexual child abuse is not something that we should take it lightly. Even though many steps have been taken by the government and NGOs, cases of sexual child abuse keep increasing every year. Therefore, it should be taken seriously and provide the way to protect the victim and to prevent it from happening. This study adopts a qualitative method. Researcher apply in-depth interview as a technique of collecting information in order to identify the factors that contribute the children to involve in sexual abuse. Four respondents have been selected to participate in this interview: selected female teenager from government shelter home, Taman Seri Puteri at Kajang. However, there are many reasons for people to engage with sexual activity as there is no continuous monitoring from their parents or caretaker. The findings revealed that parental negligence, poverty and mass media influence is the main factors in contributing to involvement in sexual abuse cases. There is a need to educate children about sexual abuse in order to increase their awareness and self-protection. This study also provides suggestions in order to tackle this issue. Lastly, it is hoped that this study could contribute in combating sexual abuse issue and able to protect children who in need of full protection from their family.